Hues of Martyrdom: Monastic and Lay Asceticism in Two Homilies of Gregory the Great on the Gospels - Hoel, Nikolas O (The Downside review, 2020)
Pope Gregory I was the first monk to hold the office of Bishop of Rome, and he was one of the most prolific papal writers of the Middle Ages. It should not be a surprise that his views on monasticism can be found in everything that he wrote, including the Homiliae in Evangelia. This text includes lessons that would be heard by both monks and lay people, because both would have been listening to the sermons. By looking at the first two of these homilies, it can be determined that Gregory urged his audience to strive for asceticism, which he equated to martyrdom. Yet, the asceticism of the monk could not be the same as that of the lay person. This article argues that Gregory conceived of two types on non-red martyrdom: the white martyrdom of the monks which served as the model for the blue martyrdom of the laity.